Acute Streptococcal Tonsillitis in a Child. Questions asked by Life (Scientific Answers to the Question Put by the Practice) - N.V. Nagornaya; Ye.V. Borgyugova; A.P. Koval (Zaslavsky O.Yu., 2013)
The problem of acute tonsillitis remains relevant in clinical pediatrics. A special role in its etiology belongs to group A β-hemolytic streptococcus (Streptococcus pyogenes), which is found in every fourth child with acute bacterial tonsillitis. In this article there is presented an analysis of the clinical case of streptococcal tonsillitis in children and the pathogen, epidemiology and prognosis of the disease are described. The authors reviewed the current diagnosis criteria and international treatment approaches. There has been grounded the use of cefuroxime axetil for eradication of Streptococcus pyogenes.